CORPORATE GOVERNANCE, MODAL INTELEKTUAL, DAN KEBIJAKAN DIVIDEN: DAMPAK TERHADAP NILAI PERUSAHAAN - Indah Sukmaningsih (2021)
This study aims to empirically examine the effect of corporate governance, intellectual capital, and dividend policy on firm value with the covid-19 pandemic as a control variable on the Kompas 100 index companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This study uses quantitative methods with secondary based on financial statements and annual reports. The sample collected on this study is 39 companies in Kompas 100 index companies using purposive sampling method. The data analysis techniques used are model specification test, classical assumption test, multiple linear regression, and hypothesis testing using simultaneous test (f test) and partial test (t test) with STATA version 16. The results show that (1) the board of commissioners is independent has no effect on firm value, (2) audit committee has a significant negative effect on firm value, (3) intellectual capital has no effect on firm value, and (4) dividend policy has a significant positive effect on firm value.